2016
DOI: 10.1186/s13068-016-0546-6
|View full text |Cite
|
Sign up to set email alerts
|

The sorghum SWEET gene family: stem sucrose accumulation as revealed through transcriptome profiling

Abstract: BackgroundSWEET is a newly identified family of sugar transporters. Although SWEET transporters have been characterized by using Arabidopsis and rice, very little knowledge of sucrose accumulation in the stem region is available, as these model plants accumulate little sucrose in their stems. To elucidate the expression of key SWEET genes involved in sucrose accumulation of sorghum, we performed transcriptome profiling by RNA-seq, categorization using phylogenetic trees, analysis of chromosomal synteny, and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
102
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(106 citation statements)
references
References 54 publications
(69 reference statements)
4
102
0
Order By: Relevance
“…Of those 41 aquaporins the expression of 16, primarily NIPs and TIPs, was relatively low. However, PIP1;2, PIP2;1 , and NIP2;2 homologs were all highly expressed in pith and rind of sorghum plants after heading, which is consistent with our findings for the S. viridis homologs of these genes ( Figure 2 ; Mizuno et al, 2016). Comparisons with other gene expression studies for C 4 grass stem tissues were not possible as in most studies the internode tissue has not been separated into different developmental zones or the study has not reported aquaporin expression (Carson and Botha, 2000, 2002; Casu et al, 2007).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Of those 41 aquaporins the expression of 16, primarily NIPs and TIPs, was relatively low. However, PIP1;2, PIP2;1 , and NIP2;2 homologs were all highly expressed in pith and rind of sorghum plants after heading, which is consistent with our findings for the S. viridis homologs of these genes ( Figure 2 ; Mizuno et al, 2016). Comparisons with other gene expression studies for C 4 grass stem tissues were not possible as in most studies the internode tissue has not been separated into different developmental zones or the study has not reported aquaporin expression (Carson and Botha, 2000, 2002; Casu et al, 2007).…”
Section: Discussionsupporting
confidence: 91%
“…In mature S. viridis internode tissues, the transcript levels of TIPs and NIPs was generally low with the exception of SvNIP2;2, SvTIP4;2 , and SvTIP1;2. In a sorghum stem transcriptome report investigating SWEET gene involvement in sucrose accumulation, we note that transcripts for all 41 sorghum aquaporins were detected in pith and rind tissues in 60-day-old plants (Reddy et al, 2015; Mizuno et al, 2016). Of those 41 aquaporins the expression of 16, primarily NIPs and TIPs, was relatively low.…”
Section: Discussionmentioning
confidence: 89%
“…Particularly, SbTST4‐1 expression in RIO was dramatically higher than those in R9188/BTx406. Comparison of SbSUT2 and SbTST4‐1 expression patterns between the three genotypes, together with similar expression profiles in other sweet sorghum lines (Bihmidine et al ., ; Mizuno et al ., ), strongly indicated roles in sucrose import for stem storage sink (Figure S20). For SWEET s, 16 genes were expressed with Sb SWEET7‐1 (Sobic.007G191200) introgressed from BTx406 into R9188.…”
Section: Resultsmentioning
confidence: 85%
“…Concomitant with the genetic and biochemical characterization of transporters, there have been correlative studies hinting at the contribution of transporter gene expression to sugar content in sink tissue. For example, transcriptomic analyses of fruit development in apple (Wei et al ., ), grape (Afoufa‐Bastien et al ., ), pear (Li et al ., ), banana (Miao et al ., ) and tomato (Reuscher et al ., ; Feng et al ., ), as well as the development of sweet sorghum stems (Mizuno et al ., ) and sugar beet roots (Jung et al ., ), all point to members of sugar transporter families in which expression patterns coincide with sugar accumulation patterns. A combined proteomic and transcriptomic study of sugar beet tonoplast membranes led to the identification and characterization of BvTST (tonoplast sugar transporter), which is likely to be responsible for the high sucrose accumulation characteristic of sugar beet roots (Jung et al ., ), and which functions in consort with the leaf phloem‐localized sucrose loading transporter BvSUT in determining a source–sink interaction influenced by respective push and pull transporters (Nieberl et al ., ).…”
Section: Discussionmentioning
confidence: 99%